Analisis Efektivitas Penggunaan Anggaran Belanja Langsung Terhadap Anggaran Berbasis Kinerja Pada Kantor Kecamatan Medan Helvetia - Edi Saputra Matondang; Juniarti Juniarti (Jurnal Riset AKuntansi dan Bisnis, 2022)
This study aims to find out the implementation used in the budget directly to the performance-based budget and to analyze the effectiveness of the budget directly against the performance-based budget at the Medan Helvetia Subdistrict office. The data source of this study is sourced from secondary data, namely data obtained from documents and archives obtained from the Medan Helvetia District Office. While the data collection techniques in this study are carried out by observation, interview and documentation studies. The data analysis technique used is a comparative descriptive analysis that uses the preparation of performance-based direct spending budgets set by the general bureau and secretarial equipment of Medan Helvetia Subdistrict.The results of research obtained the Use of Budget and Expenditure of the Medan Helvetia Subdistrict Office are quite effective. Budget and spending effectiveness ratio from 2019 effectiveness ratio of 84.22%, in 2020 effectiveness ratio of 93.33%, in 2021 effectiveness ratio of 97.7%.